Planowanie i przeprowadzanie eksperymentu naukowego w badaniach glottodydaktycznych - Rokoszewska, Katarzyna (Neofilolog, 2010)
The classic experiment is one of the most important research methods in glottodidactics. The classic experiment must fulfill two conditions, namely control and experimental groups must be formed and subjects must be assigned to these groups at random. If one of these conditions, namely randomization, is not met, the research method is called quasiexperimental. If none of the conditions is met the method is called pre-experimental. In fact, the pre-experiment is probably most often used in research on teaching and learning foreign languages because, just like the true experiment, it allows the researcher to draw conclusions about the cause and effect relationship between particular variables and, at the same time, it is more practical than the true experiment. The aim of this paper is to present the experimental procedure consisting of ten steps proposed by Clegg (1994).